Detox Media Digital (Sikap Milenial Terhadap Detox Media Digital) - Sri Wahyuning Astuti; Dyah Sri Subandiah (PRoMEDIA, 2020)
AbstractThe penetration of digital media use, especially millennials, is getting longer and more massive. In a day, on average, millennials in Indonesia use digital media for up to 5 hours per day. The use of digital media which has become increasingly massive has created problems for its users. Starting from physical problems to psychological problems. To reduce dependency and the negative impact of social media users, a digital media detox is needed. Digital media detox is an effort to reduce to select the use of digital media, from social media to the use of internet-based applications. Detox digital media aims to make users use only the applications they need. This study aims to determine the attitudes of social media users regarding digital media detox using a descriptive quantitative approach. The subjects in this study were social media users. The data collection technique used was convenience sampling. The results showed, at the cognitive, affective and conative level most of the respondents already had a positive attitude towards digital media detox.Keywords: Detox, Digital media, AttitudeAbstraksiPenetrasi penggunaan media digital khususnya milennial semakin lama dan masif. Dalam sehari rata rata milennial menggunakan media digital hingga 5 jam perhari. Penggunaan media digital yang sudah semakin masif memunculkan permasalahan bagi para penggunanya. Mulai dari masalah fisik hingga maslah psikologis. Sayangnya dampak yang ditimbulkan dari penggunaan media sosial, tidak diikuti dengan peningkatan kesadaran penggunanya. Sebagian besar pengguna media sosial bahkan tidak sadar dengan efek negatif penggunaan media sosial yang terus menerus yang mereka alami. Karena itulah diperlukan sebuah terobosan untuk mengurangi penggunaan sosial media. Langkah sederhana yang bisa dilakukan adalah dengan detox media sosial, yakni mengurangi penggunaan media sosial dan menyeleksi content yang mendatangkan pengaruh buruk bagi milennial. Sayangnya, tidak semua milennial melakukan aktifitas ini, karena persepsi dan pemahaman yang salah dari detox media sosial.Kata Kunci: detox media digital, persepsi, partisipasi